2021
DOI: 10.3390/medicina57030225
|View full text |Cite
|
Sign up to set email alerts
|

A Short History of Skin Grafting in Burns: From the Gold Standard of Autologous Skin Grafting to the Possibilities of Allogeneic Skin Grafting with Immunomodulatory Approaches

Abstract: Due to groundbreaking and pioneering developments in the last century, significant improvements in the care of burn patients have been achieved. In addition to the still valid therapeutic standard of autologous split-thickness skin grafting, various commercially available skin substitutes are currently available. Significant progress in the field of tissue engineering has led to the development of promising therapeutic approaches. However, scientific advances in the field of allografting and transplant immunol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 135 publications
0
31
0
Order By: Relevance
“…Allogeneic skin grafts catalyse potent immune responses involving both the innate and adaptive immune system, and their clinical applications need to rely heavily on effective immunosuppression in the recipient [ 93 ]. The immunocompromised state of patients with severe burn injuries receiving allogeneic skin grafts may result in delayed rejection, secondary infections, and increased scarring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Allogeneic skin grafts catalyse potent immune responses involving both the innate and adaptive immune system, and their clinical applications need to rely heavily on effective immunosuppression in the recipient [ 93 ]. The immunocompromised state of patients with severe burn injuries receiving allogeneic skin grafts may result in delayed rejection, secondary infections, and increased scarring.…”
Section: Discussionmentioning
confidence: 99%
“…Xenogeneic materials such as porcine or fish skin can be used for temporary skin coverage, particularly in large scale or severe burns to stabilise the patient until they can be treated by autologous skin grafting [ 93 ]. Xenogeneic grafts contain antigens which are recognised by the immune system as foreign, which can lead to biochemical failure of the graft or even host organism death [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a leading burden on healthcare with increasing cases in the world. The Global Burden of Disease (GBD) study reported a prevalence of 605,036,000 cases in 2015 compared to 492,883,000 cases in 2005 based on global, regional, and national data from over 195 countries and territories ( Utami et al, 2020 ; Chouhan et al, 2019 ; Schlottmann et al, 2021 ). The complete wound healing process is carried out in four main parallel steps; hemostasis, inflammation, proliferation, and remodeling ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Skin allografts and cadaveric and living donor allografts[ 14 15 16 ] provide biological wound cover with significant clinical benefits. The clinical uses of allografts include coverage of extensive full thickness wounds, meshed skin autografts,[ 17 18 ] and healing of partial thickness wounds. The benefits of the use of human skin allografts in wound coverage of burns have been well documented.…”
Section: Introductionmentioning
confidence: 99%